Computed tomography image analysis for Indonesian total hip arthroplasty designs - Talitha Asmaria; Dita Ayu Mayasari; Alfensa Dinda Gestara Febrananda; Nadiya Nurul; Ahmad Jabir Rahyussalim; Ika Kartika (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Total hip arthroplasty purposes to replace a hip joint damaged by an artificial hip joint. However, the developed products that already exist in the market lead to the mismatch between the hip implant equipment and the patient’s bone morphometric. Besides causing complications, the mismatch also continues to the dislocation effects, fracture, osteolysis, and thigh pain. This paper aims to design a customized hip implant based on real patient data, particularly for Indonesian patient, limited to the acetabular components and stem parts. The computed images were analyzed to estimate the patient proximal femur morphometric; those are the femoral head diameter, neck-shaft angle, mediolateral width, anteroposterior width, neck length and neck width. The experiment has succeeded in designing the acetabular shell with the thickness of 3 mm, the acetabular liner with the thickness of 6 mm, the femoral head between 22.4 to 24.8 mm, the short stem in both the right for 110.656 mm and left femur bone for 111.49 mm; that fit the patient's femur bone. Overall, the proposed steps in designing the customized hip implant in this work, based on image analysis on medical imaging data, can be a standard to be applied for other patient-needs hip arthroplasty implants.